Study of the Penetration Bias of ENVISAT Altimeter Observations over Antarctica in Comparison to ICESat Observations - Aurélie Michel; Thomas Flament; Frédérique Rémy (Remote Sensing, 2014)
The aim of this article is to characterize the penetration bias of the ENVIronmental SATellite (ENVISAT) radar altimeter over the Antarctic ice sheet through comparison with the more accurate measurements of the Ice, Cloud and land Elevation Satellite (ICESat) altimeter at crossover points. We studied the difference between ENVISAT and ICESat fluctuations over six years. We observed the same patterns between the leading edge width and the elevation difference. Both parameters are linked, and the major bias is due to the lengthening of the leading edge width due to the radar penetration. We show that the elevation difference between both altimeters and the leading edge width are linearly well-linked with a 0.8 Pearson correlation coefficient, whereas the slope effect over the coasts is difficult to analyze. When we analyze each crossover point temporal evolution locally, the linear correlation between the leading edge width and the elevation difference is between −0.6 and −1. Fitting a linear model between them, we find a reliability index greater than 0.7 for the Antarctic Plateau and Dronning Maud Land, which confirms that the penetration effect has a linear influence on the retrieved height. Moreover, we present results from SARAL/AltiKa (launched in February 2013) that confirm SARAL/AltiKa accuracy and the promising information it will provide.